2019
DOI: 10.1002/anie.201811391
|View full text |Cite
|
Sign up to set email alerts
|

Gasotransmitter Regulation of Phosphatase Activity in Live Cells Studied by Three‐Channel Imaging Correlation

Abstract: Enzyme activity in live cells is dynamically regulated by small‐molecule transmitters for maintaining normal physiological functions. A few probes have been devised to measure intracellular enzyme activities by fluorescent imaging, but the study of the regulation of enzyme activity via gasotransmitters in situ remains a long‐standing challenge. Herein, we report a three‐channel imaging correlation by a single dual‐reactive fluorescent probe to measure the dependence of phosphatase activity on the H2S level in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…With this desire in mind, Yu et al reported a new FRET system in 2019 that could be used for monitoring DC m levels through readout of a ratiometric fluorescence signal. 40 The FRET system was constructed using a carbazole linked to a benzyl chloride functionalized pyridinium group (48) as the fluorescent donor and a quinoline derivative providing for an extended D-p-A structure (49) as the fluorescence acceptor (Fig. 30).…”
Section: Fret-based Sensors For the Visualisation Of Cellular Microenmentioning
confidence: 99%
See 2 more Smart Citations
“…With this desire in mind, Yu et al reported a new FRET system in 2019 that could be used for monitoring DC m levels through readout of a ratiometric fluorescence signal. 40 The FRET system was constructed using a carbazole linked to a benzyl chloride functionalized pyridinium group (48) as the fluorescent donor and a quinoline derivative providing for an extended D-p-A structure (49) as the fluorescence acceptor (Fig. 30).…”
Section: Fret-based Sensors For the Visualisation Of Cellular Microenmentioning
confidence: 99%
“…30). Initially, the fluorescent donor (48) was immobilized to the mitochondria by means of covalent bonds formed between the benzyl chloride moiety of 48 and endogenous protein thiol groups localised in the mitochondria. In this state, 48 displayed a fluorescence signal (green channel, 510-550 nm) under excitation at 405 nm, irrespective of changes in the DC m .…”
Section: Fret-based Sensors For the Visualisation Of Cellular Microenmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Zhang constructed a two-response site uorescent probe for simultaneously sensing H 2 S and phosphatase via two independent uorescence signal channels (probe 60). 79 The H 2 S-responsive uorophore coumarin derivative (emission at 445 nm) was linked to rhodol (emission at 545 nm) which served as a phosphate-reactive dye. More importantly, through combination with the FRET signal between rhodol and coumarin uorescence signals, the authors established a three-channel strategy to detect and image H 2 S and phosphatase activity and investigate the correlation between them in living cells.…”
Section: Azide Reductionmentioning
confidence: 99%
“…[6] More recently, super-resolution nanoscopy aided by membrane-penetrating inorganic carbon dots has achieved dynamical tracking of nucleic acids in cells and C. elegans. [7] In parallel, al arge number of fluorescent probes have been developed to detect ROS, [8] enzymes [9] and other biological analytes [10] in live cells, but most of them exhibit optical properties undesirable for multicolor super-resolution imaging such as limited by small Stokes shift and photostability. [11] Furthermore,these imaging agents all have different chemical properties and intracellular biodistributions,m aking multi-analyte imaging in the same cell compartment extremely difficult.…”
Section: Introductionmentioning
confidence: 99%